Edible flowers as an emerging horticultural product: A review on sensorial properties, mineral and aroma profile - Pires, Eleomar de O.; Di Gioia, Francesco; Rouphael, Youssef; García-Caparrós, Pedro; Tzortzakis, Nikos G.; Ferreira, Isabel C. F. R.; Barros, Lillian; Petropoulos, Spyridon A.; Caleja, Cristina (My University, 2023)
Background: The current consumer needs for functional and healthy foods, as well as for diversified diets that include a variety of food sources have created a market niche for novel horticultural products such as edible flowers and related food formulations. Scope and approach: Considering the increasing interest on this crop production sector during the last few years, this review aims to compile the most relevant data regarding the production and marketing aspects of edible flowers, focusing on pre- and postharvest parameters that should be taken into account to facilitate their successful marketing. Moreover, this review presents the most important flower species that have been traditionally used or suggested for edible uses, while the sensorial attributes and the mineral profile of edible flowers are also presented. A special section is dedicated to the aroma components and the essential oils of several flower species focusing on those reports which refer to species with edible uses, while the bioactivities of these compounds are also cited. Finally, future remarks regarding the next steps that are required for the establishment of this new food segment in the market and the consumer awareness for related products are discussed. Key findings and conclusions: Edible flowers is a promising and challenging horticultural crop which could provide alternative solutions to farmers under the ongoing climate changing, having also in mind the sustainable use of natural resources, the diversification of agroecosystems and the preservation of biodiversity. Moreover, food industry could benefit by covering market demands for functional and healthy foods through the development of novel floral-based foods and food formulations, thus allowing the valorization of species that are unexplored or underexplored so far.
Keywords: Macrominerals; Essential oils; Volatile compounds; Functional properties; Terpenoids; Bioactive properties